2013
DOI: 10.1093/nar/gkt1027
|View full text |Cite
|
Sign up to set email alerts
|

ppdb: plant promoter database version 3.0

Abstract: ppdb (http://ppdb.agr.gifu-u.ac.jp) is a plant promoter database that provides information on transcription start sites (TSSs), core promoter structure (TATA boxes, Initiators, Y Patches, GA and CA elements) and regulatory element groups (REGs) as putative and comprehensive transcriptional regulatory elements. Since the last report in this journal, the database has been updated in three areas to version 3.0. First, new genomes have been included in the database, and now ppdb provides information on Arabidopsis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 16 publications
1
37
0
Order By: Relevance
“…Both the cis-regulatory ABA-responsive promoter elements (ABREs) and homologs of transacting factors from the ABF/ABI5 subfamily of bZIP transcription factors binding to ABREs in promoters of ABA-responsive genes have been found in the moss Physcomitrella [19,[24][25][26]. To gain deeper insights into the evolution of fast ABA signaling leading to stomatal closure, we asked the following question: when did early land plants start to use the ancient ABA-dependent drought stress-signaling pathway to control stomatal transpiration ( Figure 1B)?…”
Section: Resultsmentioning
confidence: 99%
“…Both the cis-regulatory ABA-responsive promoter elements (ABREs) and homologs of transacting factors from the ABF/ABI5 subfamily of bZIP transcription factors binding to ABREs in promoters of ABA-responsive genes have been found in the moss Physcomitrella [19,[24][25][26]. To gain deeper insights into the evolution of fast ABA signaling leading to stomatal closure, we asked the following question: when did early land plants start to use the ancient ABA-dependent drought stress-signaling pathway to control stomatal transpiration ( Figure 1B)?…”
Section: Resultsmentioning
confidence: 99%
“…The RAR was calculated as the ratio of the frequency of each octamer unit in the promoter of the grouped genes to that in the promoters of genome-wide genes. The promoter was defined as -1,000 bp from the TSS reported in the Plant Promoter Database (ppdb; http://ppdb.agr.gifu-u.ac.jp; Hieno et al, 2014). The RAR value of each octamer unit was plotted on the 0-to -540-bp region of the AtALMT1 promoter and statistical significance (P , 0.05) was assessed with Fisher's exact test.…”
Section: Prediction Of Cis-acting Elements In the Atalmt1 Promotermentioning
confidence: 99%
“…As a first step, we searched the database composed of 24,956 promoters (Hieno et al, 2014) for genes containing Elements A and B in the promoter region. A total of 236 genes containing Element A and 71 genes containing Element B in the promoter region was identified (Supplemental Table S1).…”
Section: Expression Profile Of Genes Containing Elements a And Bmentioning
confidence: 99%
“…The promoter sequences used for prediction in this study included a set of 14,959 promoters whose positions have been experimentally identified (Yamamoto et al, , 2011 or a new set composed of 24,956 promoters redetermined by sequencing of 34 million transcription start site tags (Hieno et al, 2014). This analysis evaluates the degree of overrepresentation of each octamer in some stressresponsive promoters identified by microarray analysis over total promoters in an analyzed genome.…”
Section: Prediction Of Regulatory Elements In the Elip2 Promoter And mentioning
confidence: 99%